El control de concentraciones en mercados financieros en la política antitrust en Brasil - Bagnoli, Vicente (2022)
The financial market, in general, has specific characteristics that attract the attention of competition authorities around the world. It is no different in Brazil, where the trend of bank concentration in recent decades has put CADE, the competition authority, on constant alert. In this sense, since the entry into force of the Competition Law in 2012, CADE has analyzed significant concentrations in financial markets. In addition to CADE, the Central Bank of Brazil also analyzes concentrations in the financial system. The conflict of jurisdiction between the Central Bank of Brazil and CADE in competition matters generated legal uncertainty, but the 2018 Memorandum of Understanding between the authorities brought more certainties to the market. However, a Memorandum is not legally binding for the authorities and may be revised at any time.